APLIKASI PUPUK ORGANIK CAIR SABUT KELAPA UNTUK MENINGKATKAN HASIL BAWANG MERAH (Allium ascalonium L.) - Okti Purwaningsih (Fakultas Pertanian Universitas Janabadra, 2025)
Coconut husk and waste can be used as liquid organic fertilizer (POC) to improve soil fertility due to the nutrient content contained in coconut coir. The use of coconut fiber as POC needs to be assessed to obtain recommendations for the correct concentration and application interval. This study aimed to examine the effect of coconut fiber POC application on shallot growth and yield, and determine the optimal concentration that can provide the best results. The study used RCBD (Randomized Completely Block Design) in three replications, consisting of two factors. The first factor was the concentration of the coconut fiber POC solution: control, 10%, 20%, and 30%. The second factor is the time interval of coconut fiber POC application, namely 1, 2, and 3 weeks. The variables observed in this study were the number of tillers per clump, number of tubers, fresh weight of tubers, dry weight of tubers, and tuber diameter. Data were analyzed using Analysis of Variance (ANOVA) at a significance level of 5%. The results showed that applying coconut fiber POC concentrations of 10%, 20%, and 30% increased the number of tillers per clump, dry bulb weight, and diameter of shallot bulbs, but there were no significant differences among the three concentrations. The results of the regression analysis showed that the optimum concentration was in the range of 17%–18.26%. The time interval for applying coconut fiber POC has no significant effect on increasing the number of tillers per clump, the number of bulbs.